2022
DOI: 10.1177/10778012221083328
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Policy and Programming on Female-Victim Intimate Partner Homicide at the County Level in Florida

Abstract: Legal and social service interventions aim to mitigate intimate partner violence (IPV) and keep IPV from becoming lethal. Accordingly, this study examines the impact of policies and programs on female-victim intimate partner homicide (FVIPH) rates across the 67 counties of the state of Florida. It focuses on community coordinated response efforts, batterer intervention programs, local domestic violence (DV) ordinances, DV fatality review teams, and DV shelter programs. Results indicate that community coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…The intervention helps victims by replacing sheltering with offender monitoring and ensuring victim safety (Messing and Campbell, 2016). With coordinated community response efforts as the only intervention associated with fatal violence, it can be concluded that risk-informed, victim-centered interventions that integrate providing information about social services/resources may decrease the incidence of lethal violence (Montanez et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The intervention helps victims by replacing sheltering with offender monitoring and ensuring victim safety (Messing and Campbell, 2016). With coordinated community response efforts as the only intervention associated with fatal violence, it can be concluded that risk-informed, victim-centered interventions that integrate providing information about social services/resources may decrease the incidence of lethal violence (Montanez et al , 2020).…”
Section: Introductionmentioning
confidence: 99%